(untitled) (PUBMET, 2023)
Modern electronic publishing enables faster and easier access to information and scientific publications. Unfortunately, misleading publishing practices have adapted and become harder to identify. It is not only the publication in these journals and publishers that is questionable but also the citation of these sources. We find that such unverified and unreviewed scientific publications can negatively impact the society as a whole. Regrettably, even at the University of Maribor, we are seeing an increase in the use and adoption of such sources. As a result, the University of Maribor Library has compiled a private list of predatory publishers according to our own criteria, we provide further education, create LibGuides, and maintain a public list of open access sources. We also offer advice on checking journals, publishers, and conferences. This includes both students, who should be cautious in the selection and use of sources, as well as lecturers and researchers, who should be careful not just in the selection and use of sources but also in the selection of reputable journals for publication. The very process of submitting the final student theses to the institutional repository includes content similarity detection. Content similarity detection is also available to any University of Maribor researcher who wants to double-check their article before publication. Our practices of raising awareness about unverifiable sources will be presented in more detail on the poster.